2021
DOI: 10.3390/cancers13236082
|View full text |Cite
|
Sign up to set email alerts
|

An Intersectional Perspective on the Utilization of Cervical Cancer Screening among Migrants. A Cross-Sectional Analysis of Survey Data from Austria

Abstract: In most European countries, migrant women have lower rates of cervical cancer screening utilization than non-migrant women. While studies have illustrated that disparities can be partially explained by social determinants, they usually did not take into account the heterogeneity of the migrant population in terms of cultural background or country of origin. Applying an intersectional approach and using 2019 data from a representative survey from Austria on 6228 women aged 20–69 years, the present study examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
1
2
1
5
Order By: Relevance
“…This counter-intuitive finding contradicts previous research which showed that older migrants are more disadvantaged than younger individuals [66]. However, similar were reported in other studies [42]. Given that the interaction effects in the present study were not significant, further investigations are needed.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This counter-intuitive finding contradicts previous research which showed that older migrants are more disadvantaged than younger individuals [66]. However, similar were reported in other studies [42]. Given that the interaction effects in the present study were not significant, further investigations are needed.…”
Section: Discussioncontrasting
confidence: 99%
“…Disparities could be explained by different barriers migrants encounter in health care, comprising poor German language proficiency, a low health literacy or cultural needs not sufficiently addressed by health care facilities [40,41]. Several investigations from Germany and other countries have also shown that disparities may vary by sex or age [26,[42][43][44], emphasizing the need for an intersectional perspective. However, findings are not consistent across the available data, as not all studies identified disparities between both population groups [45] and others reported a higher utilization among migrants than non-migrants [46].…”
Section: Introductionmentioning
confidence: 99%
“…Por sua vez, não apenas na América do Sul, há mulheres que evitam os serviços de saúde ( 2 , 3 , 11 ) e outras que conseguem acessá-los, mas recebem cuidado inadequado ou de pior qualidade, não por ausência de cobertura e/ou acesso ao rastreamento, mas por iniquidades derivadas de discriminação institucional ( 55 ). Ademais, mulheres de baixa renda ( 48 , 53 ), grupos étnicos ( 11 , 41 ), mulheres com deficiência ( 55 ) e mulheres negras ( 64 ), além da população bissexual, lésbica e transgênero ( 13 ), experimentam maiores desafios relacionados ao controle do CCU. Por consequência, as políticas públicas de saúde da mulher carecem de uma perspectiva interseccional ( 11 ).…”
Section: Discussionunclassified
“…A atenção primária à saúde (APS), um componente-chave dos sistemas de saúde ( 6 ), tem função central no controle do CCU ( 7 - 9 ). A persistência de altas taxas de mortalidade por CCU associa-se a inadequações nos sistemas de saúde ( 1 ), barreiras de acesso ao rastreamento, cobertura insuficiente ( 2 - 4 , 10 ) e dificuldade de atenção numa perspectiva interseccional ( 11 ). Entretanto, embora uma estrutura de saúde e uma assistência adequadas sejam requisitos fundamentais para melhorar o controle do CCU ( 7 ), são insuficientes ( 8 ); aspectos como valores culturais das mulheres ( 9 ) e discriminação institucional por questões étnicas ( 12 ), sexuais e de gênero ( 9 , 11 , 13 ) interferem na qualidade e na adesão ao rastreamento.…”
unclassified
See 1 more Smart Citation